Does the radiofrequency impedance-controlled endometrial ablation have any morphologic effects on uterine leiomyomata?: Report of 3 cases - Fadare Oluwole; Wang Sa A; Renshaw Idris L (BMC, 2008)
Abstract A variety of novel endometrial ablation technologies are now in routine use. A subset of uteri that had previously undergone these treatments will ultimately be evaluated by the pathologist. However, the full spectrum of histologic changes that may result from these treatments has received only sporadic attention. The NovaSure™ [Hologic Corporation, Marlborough, MA, USA] endometrial ablation system is one of several available second-generation technologies and its particular endometrial ablative power is based on the delivery of radiofrequency energy. The present analysis was designed to decipher any histologic changes (if any) associated with the NovaSure™ endometrial ablation system relative to benign smooth muscle tumors of the uterine corpus. Over a one-year period, 3 uteri that had previously undergone the NovaSure™ endometrial ablation and which also had leiomyomatous mass lesions were evaluated. The leiomyomatous mass lesions were extensively sampled and were evaluated for cellular shapes (epithelioid change, cellular rounding, extraordinary cytoplasmic eosinophilia, clear cell change, cytoplasmic vacuolation), nuclear changes (nucleomegaly, nucleolomegaly, multinucleation, hyperchromasia, symplastic changes), necrosis (coagulative and/or infarct), mitotic activity, apoptotic bodies or pyknotic cells, myxoid change, hyalinization. The three uteri were resected 61, 47 and 74 (mean 60.7) days post-ablation. After a detailed evaluation of multiple submucosal, intramural and subserosal leiomyomata from these 3 uteri, no noteworthy histologic changes were identified in the tumors. Since the presence or absence of tumor necrosis is one histologic criterion by which malignant potential is assigned to uterine smooth muscle neoplasms, defining any extrinsic processes that may establish, or contribute to this finding is clinically relevant. The findings reported herein suggests that if a leiomyoma that was obtained from a patient that had recently undergone the NovaSure™ endometrial ablation displays any degenerative changes such as necrosis, the changes are probably not attributable to the ablation.